Dkk‐1–Mediated Inhibition of Wnt Signaling in Bone Ameliorates Osteoarthritis in Mice. Issue 11 (November 2014) - Funck‐Brentano, Thomas; Bouaziz, Wafa; Marty, Caroline; Geoffroy, Valerie; Hay, Eric; Cohen‐Solal, Martine
<x xml:space="preserve">Abstract</x> Objective Wnt signaling is a master regulator of joint homeostasis, but its role in osteoarthritis (OA) remains unclear. This study was undertaken to characterize the activation of Wnt/β‐catenin in knee joints of mice with OA and to assess how inhibiting this pathway in bone could affect cartilage. Methods OA was induced by partial meniscectomy in Topgal mice and in transgenic mice overexpressing Dkk‐1 under the control of the 2.3‐kb Col1a1 promoter (Col1a1‐Dkk‐1–Tg mice). Wnt/β‐catenin activation was assessed by X‐Gal staining at baseline and at weeks 4, 6, and 9. Cartilage and bone damage was analyzed in Col1a1‐Dkk‐1–Tg mice with OA at week 6. Primary chondrocytes and cartilage explants were used to assess the effect of Dkk‐1 on cartilage catabolism. Results In meniscectomized Topgal mice, Wnt was mainly activated in osteocytes from the subchondral bone at week 6 after OA induction, as well as in osteophytes and synovium at week 4. Chondrocytes from damaged zones expressed X‐Gal from week 4. Dkk‐1 expression was high in chondrocytes in control mouse knees (mean ± SEM 84.2 ± 3.1%) but decreased greatly in knees of meniscectomized mice from week 4 (mean ± SEM 14.4 ± 3.8%). The OA score was lower in meniscectomized Col1a1‐Dkk‐1–Tg mice at week 6 compared with wild‐type mice (5.1 ± 0.6 versus 8.4 ± 0.6; P = 0.002). Subchondral bone fraction and osteophyte volume were decreased. However, cartilage explants from Col1a1‐Dkk‐1–Tg mice showed proteoglycan loss and increased NITEGE expression. Expression of vascular endothelial growth factor (VEGF) was reduced in osteoblasts from Col1a1‐Dkk‐1–Tg mice, thereby decreasing expression of messenger RNA for matrix metalloproteinases in chondrocytes. Conclusion Wnt activation in OA affects the whole joint, particularly bone. Selective inhibition of this pathway in bone by Dkk‐1 decreased OA severity through VEGF inhibition.